Synthesis, Characterization and Thermal Stability of Nanocrystalline MgAlMnFeCu Low-Density High-Entropy Alloy - Pandey V.K.; Shadangi Y.; Shivam V.; Basu J.; Chattopadhyay K.; Majumdar B.; Sarma B.N.; Mukhopadhyay N.K. (My University, 2025)
An equiatomic quinary MgAlMnFeCu high-entropy alloy (HEA) has been synthesized successfully by mechanical alloying (MA). Phase evolution of MgAlMnFeCu HEA has been studied using X-ray diffraction (XRD), transmission electron microscopy (TEM) and energy-dispersive spectroscopy (EDS/XEDS). Milling up to 60 h leads to the formation of a mixture of two phases consisting of a BCC phase (a = 2.87 ± 0.02 Å) and ϒ-brass-type phase (a = 8.92 ± 0.03 Å), with ~ 2 μm powder particle size. The as-milled alloy after spark plasma sintering (SPS) at 900 °C exhibits an experimental density of 4.946 ± 0.13 g cc−1, which is 99.80% of the theoretical density. SPS leads to the formation of C15 Laves phase (MgCu2-type; a = 7.034 ± 0.02 Å) and B2 (AlFe-type; (a = 2.89 ± 0.02 Å) intermetallic along with the ϒ-brass-type phase. The SPSed sample has exceptional hardness value (~ 5.06 GPa), high compressive strength (~ 1612 MPa) and appreciable failure strain (~ 6.4%) coupled with relatively low density. Various thermodynamic parameters have been considered for understanding the phase evolution and their stability during MA. © 2020, The Indian Institute of Metals - IIM.